Petroleum Sector and Exchange Rate Appreciation in Nigeria - Kunemoemi, Zacchaeus (NIU Journal of Management Sciences, 2026)
This paper investigates the impact of Petroleum Sector on Exchange Rate Appreciation in Nigeria over the period 1990–2025. Crude Oil Production, Crude Oil Export, Oil Export Revenue and OPEC Quota Compliance were used as a proxy for petroleum sector while exchange rate was used as a stand in for exchange rate appreciation. Secondary data were sourced from the Central Bank of Nigeria (CBN) Statistical Bulletin, NNPCL OPEC Report Various Issues 2025. The Augmented Dickey-Fuller unit root test was employed to examine the stationarity properties of the variables, while Johansen Co-integration and Ordinary Least Square analysis were utilized to estimate short-run.  The empirical result showed that crude oil export and oil export revenue had a negative and significant relationship with exchange rate while crude oil production exhibited a positive and significant relationship with exchange rate. However, OPEC quota compliance reported a negative and insignificant relationship with exchange rate. The study concludes that petroleum sector remains a critical lever in influencing exchange rate in Nigeria. It was recommended amongst other that the Nigerian Upstream Petroleum Regulatory Commission and Nigerian National Petroleum Company Limited should intensify efforts toward increasing and sustaining crude oil production by investing in modern extraction technologies, strengthening pipeline surveillance, and reducing operational disruptions in oil-producing regions. This will ensure consistent foreign exchange inflows and support currency stability. Keywords: Crude Oil Production, Crude Oil Export, Oil Export Revenue, OPEC Quota Compliance Exchange Rate